APPLICATION OF MODERN INFORMATION TECHNOLOGIES IN THE ASPECT OF INCREASING STUDENTS' MOTIVATION FOR PHYSICAL EDUCATION - Yahshieva Mehrinigor Shavkatovna (International Engineering Journal For Research & Development, 2021)
The article discusses the use of information technology capabilities, in particular Smart mobile applications, in order to motivate students to engage in physical education and introduce them to a healthy lifestyle